Mortality and Morbidity Colostomy Closure - Arif, Muhammad (Journal of Postgraduate Medical Institute, 2011)
A Retrospective review of 50 colostomy closure cases has been made: the patients were operated during 1984-85 in Surgical B Unit PGMI, LRH Peshawar, 40 were extra-peritoneal and 10 intra-peritoneal; 30 closures were performed in 2 layers and 20 in single layer. There were post-operative complications in 10 cases: one patient died of peritonitis and 9 cases developed complications ranging from infection to faecal fistula. Patients with complications stayed in the hospital for a longer period. The incidence of complications was more or less the same in intra-peritoneal closure except for incisional hernia which developed only in extra-peritoneal closure. Pre-operative barium studies, chemotherapeutic bowel preparation and insertion of a wound drain did not reduce the incidence of complications. The time for closure was 2-3 months after formation of colostomy.